If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9t + -6 + -6t = 0 Reorder the terms: -6 + 9t + -6t = 0 Combine like terms: 9t + -6t = 3t -6 + 3t = 0 Solving -6 + 3t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3t = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 3t = 0 + 6 3t = 0 + 6 Combine like terms: 0 + 6 = 6 3t = 6 Divide each side by '3'. t = 2 Simplifying t = 2
| 336-3x=4x | | 65h=130(h-3) | | 7+2m-1=6m+7-3m | | 36-3=0 | | (x+2)(x-4)+3x+1=0 | | 4(y-8)=3(2y-8) | | 2[m+3(2m-3)]=6(m-7) | | 7-10x=73-24x | | g(x)=-x^3+1 | | -4(r+6)=63 | | b=x^2+4bx+13 | | -8(x+3)=-88 | | 3xyz-2z^2+xy=10-2xz | | 4n^2-12n+9=0 | | 18=2l+2(6) | | 0.80x+0.45(160)=0.40(142) | | y=x^2+4bx+13 | | 7a^2+11a-6=0 | | y/6=-2 | | 5x+45=10x+1 | | 12x^2-32x=0 | | 5m-28=-12+m | | -5x-7=3x+11 | | -1=y/20 | | 5z-4z=5z+6+2z | | 5m-28=12+m | | 5y^2-17y-12=0 | | -23+31= | | 5z-9z=3z-2+5z | | 0=16t^2-640t-6400 | | -4x+32=4x-32 | | 2(10x-6)=4(5x-3) |